Severe Weather Events over Southeastern Brazil during the 2016 Dry Season - Amanda Rehbein; Lívia Márcia Mosso Dutra; Tercio Ambrizzi; Rosmeri Porfírio da Rocha; Michelle Simões Reboita; Gyrlene Aparecida Mendes da Silva; Luiz Felippe Gozzo; Ana Carolina Nóbile Tomaziello; José Leandro Pereira Silveira Campos; Victor Raul Chavez Mayta; Natália Machado Crespo; Paola Gimenes Bueno; et al. (Advances in Meteorology)
Southeastern Brazil is the most populated and economically developed region of this country. Its climate consists of two distinct seasons: the dry season, extending from April to September, the precipitation is significantly reduced in comparison to that of the wet season, which extends from October to March. However, during nine days of the 2016 dry season, successive convective systems were associated with atypical precipitation events, tornadoes and at least one microburst over the southern part of this region. These events led to flooding, damages to buildings, shortages of electricity and water in several places, many injuries, and two documented deaths. The present study investigates the synoptic and dynamical features related to these anomalous events. The convective systems were embedded in an unstable environment with intense low-level jet flow and strong wind shear and were supported by a sequence of extratropical cyclones occurring over the Southwest Atlantic Ocean. These features were intensified by the Madden–Julian oscillation (MJO) in its phase 8 and by intense negative values of the Pacific South America (PSA) 2 mode.